Ekonomi Islam dalam Menjawab Tantangan Ketimpangan Sosial Global - Siti Nuraida; Hamdiah Hamdiah; Erwan Setyanor (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Global social inequality remains one of the fundamental challenges in the contemporary world economic system. The dominance of capitalist economic structures, which emphasize growth and capital accumulation, has proven effective in stimulating economic progress; however, it has simultaneously widened the gap between wealthy and disadvantaged groups at both national and global levels. Meanwhile, socialist economic systems that prioritize income equalization continue to face limitations related to efficiency and innovation. This article aims to examine the role of Islamic economics as an alternative economic framework capable of addressing the challenge of global social inequality. The study employs a qualitative descriptive approach through a literature review of classical and contemporary sources related to global economic systems. The findings indicate that Islamic economics offers a more balanced paradigm by integrating principles of distributive justice, ethical values, and social responsibility within economic activities. Instruments such as zakat, infaq, sadaqah, waqf, along with the prohibition of riba and other exploitative economic practices, serve as essential mechanisms for reducing social inequality. Therefore, Islamic economics holds significant potential as both a normative and practical solution for promoting sustainable global economic justice.